2009
DOI: 10.1002/adv.20167
|View full text |Cite
|
Sign up to set email alerts
|

A novel process for continuous thermal embossing of large‐area nanopatterns onto polymer films

Abstract: Hot embossing and nanoimprinting processes are being widely practiced in industry. Fast and reliable production of micro/nanofeatured patterns on large‐area polymer films is of a great importance. In this study, a novel roll‐to‐roll thermal imprinting process was developed, capable of providing a mold‐heating rate of 125°C/s with sufficient temperature control to produce large‐area patterns continuously at a rapid production rate. With this new process, selected micro/nano patterns were produced on a polyethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
0
33
1
1
Order By: Relevance
“…The system can be operated stably at a high take-up speed exceeding 10 m/min. This rate is considerably higher than that previously reported by the authors [10] on a thermal roller-imprinting system. These results seem promising in that microfeatures can be successfully replicated by a robust and scalable industrial process suitable for large-area, continuous production.…”
Section: Experimental Investigationcontrasting
confidence: 61%
See 1 more Smart Citation
“…The system can be operated stably at a high take-up speed exceeding 10 m/min. This rate is considerably higher than that previously reported by the authors [10] on a thermal roller-imprinting system. These results seem promising in that microfeatures can be successfully replicated by a robust and scalable industrial process suitable for large-area, continuous production.…”
Section: Experimental Investigationcontrasting
confidence: 61%
“…Besides contact heating, active heating methods can also be utilized to heat the belt mold. Fagan et al [10] demonstrated that a belt mold can be rapidly heated by induction heating, and a temperature difference of more than 200 °C can be achieved in continuous roller imprinting. With this imprinting system, they were able to replicate both micrometer and sub-micrometer patterns at a film feed speed exceeding 1.5 m/min.…”
Section: Introductionmentioning
confidence: 99%
“…[ 103,111 ] Molding is also compatible with roll-to-roll manufacturing, but the fl ow rate into the mold pattern and curing speed is a critical factor in determining the maximum throughput speed. [ 104 ] Solution processing can even be integrated with textile substrates, which are conformal and robust. However due to the high roughness and porosity of textiles, they are best suited for devices that require thick active layers such as batteries.…”
Section: Reviewmentioning
confidence: 99%
“…Among the master materials for imprinting on glass, nickel alloy is considered more suitable as master material (Fagan et al 2010). With incorporation of other elements such as iron, copper, cobalt or manganese, the nickel alloys exhibit not only, high hardness and strength, but also high resistance to corrosion and low thermal expansion which has great contribution to avoiding deformation during imprinting (Cao et al 2007).…”
Section: Introductionmentioning
confidence: 99%